Health management as a health-saving technology among healthcare workers - P. O. Ramensky (Здоровье мегаполиса)
Introduction. Healthcare workers are one of the most important resources in the healthcare. It seems that the healthcare sector is more labor-intensive than other industries. The quality of medical services is maintained and improved through the good management of healthcare personnel and the creation of safe workplaces protecting from occupational hazards. However, the systemic management approaches to the use of health-saving technologies by medical workers play a more important role for maintaining own health. The purpose of this study is to consider the issue of maintaining health by health workers through the implementation of health management into their own life.Materials and methods. The author studied Russian and foreign sources and presented analytical data based on content analysis.Results. The study showed that the systematic introduction of preventive health promotion measures and the application of health management concept in the life of each health worker increased the performance, efficiency and stress resilience of the personnel as well as the engagement in the healthy lifestyle programs.